Controle de conyza Bonariensis com glyphosate associado a adjuvantes aplicados com diferentes pontas de Pulverização - do Espírito Santo, Tiago Lima; de Mendonça, Cristiane Gonçalves; Graichen, Felipe André Sganzerla; Raetano, Carlos Gilberto [UNESP]; Teodoro, Paulo Eduardo (My University, 2017)
The study aimed to evaluate the control of Conyza bonariensis in delayed post-emergence stage using different spray nozzles and solutions with and without adjuvants; and to verify the occurrence of resistance to glyphosate, determining the dose-response curve. The experimental design was randomized in factorial (6 spray nozzles x 5 spray solution) in twenty repetitions. The treatments were represented by spray nozzles: XR 110015 XR 11002, TT 11002 AIXR 11002, AIC 11002 and AI 11002. Tested spray solution were: glyphosate; glyphosate + Nimbus®; glyphosate + Agral®; Glyphosate + LI-700® and without herbicide application. The use or not of adjuvants in the spray solution did not differ statistically from the solution containing the herbicide only. The spray nozzles AIXR 11002, TT 11002 and XR 11002 presented best results of control the horseweed from the evaluation of 07 days after application (DAP) and 28 DAP and such spray nozzles maintained the best average of control percentage. The higher dry matter reductions of horseweed were obtained by spray nozzles 110015 XR, TT 11002 and 11002 XR compared with the control. The population evaluated presents biotypes that resist to doses of 2.880 g.ha-1 a.e. of glyphosate. It is concluded that the evaluated biotypes presents tolerance to glyphosate, independent of your association or not with adjuvants.
Control of Conyza bonariensis with glyphosate associated to adjuvants applied with different spray nozzles
Keywords: Glyphosate; Horseweed; Resistance; Spray Systems; Surfactante